2019
DOI: 10.1088/1742-6596/1179/1/012014
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Fractional Diffusion Equation via QSGS iterations

Abstract: We investigate the application of Quarter-Sweep Gauss-Seidel (QSGS) iterative method for solving (SFPDE’s) space-fractional partial diffusion equations with Dirichlet boundary condition. To do this, implicit finite difference scheme and Caputo’s derivative operator are used to discretize one-dimensional linear space-fractional equation to form system of linear equations. Then basic ideas formulation and application of the suggested iterative method are also introduced. Numerical examples of tested problems wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Based on our short review of the existing solution methods, many researchers have suggested the finite-difference method. The method of finite difference can be implicit or explicit, depending on its stability to obtain the solution [6][7][8][9][10]. Since SFDE involves changing the time and space of a continuous variable, numerical treatment such as finite difference discretization is necessary to transform the differential equation into a finite system of linear equations that a computer can solve.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our short review of the existing solution methods, many researchers have suggested the finite-difference method. The method of finite difference can be implicit or explicit, depending on its stability to obtain the solution [6][7][8][9][10]. Since SFDE involves changing the time and space of a continuous variable, numerical treatment such as finite difference discretization is necessary to transform the differential equation into a finite system of linear equations that a computer can solve.…”
Section: Introductionmentioning
confidence: 99%
“…Since the sparse and large-scale linear system's coefficient matrix is difficult to be solved analytically, an iterative method is employed as an alternative. In terms of the efficiency of the iterative processes, many authors [8,15,16] have suggested and debated over several numerical iterative methods. Besides that, the block iteration has been presented [17] to show the computation cost efficiency improvement by separating systems of equations.…”
Section: Introductionmentioning
confidence: 99%
“…The partial differential equation (1) arises, for example, in flow of incompressible fluids, gas flow in porous media, nonlinear process of heat transfer and image processing. Equation 1itself represents a nonlinear diffusion process.…”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of Quarter-Sweep approach by Othman and Abdullah [10], it has been studied by few researchers which can be referred in Eng et al [5], Sunarto and Sulaiman [1], Suardi et al [11], Aruchunan et al [4], and Nusi and Othman [12]. In contrast to these works, in the present article, we attempt to apply the Quarter-Sweep into the formulation of finite difference approximation for 1D PME.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation